The role of space in Spanish television fiction. The «Antidisturbios» Case (Movistar+, 2020) (Communication & Society, 2023)
The main objective of this research was to analyse the spatial representation constructed in the fiction TV series Antidisturbios (Riot Police) (Movistar+, 2020). It sought to look at how space is constructed in the narrative, consider the role it plays in it, and assess whether space reflects a specific sense of location related to Spanish identity. A methodology based on textual analysis was used, with emphasis on spatial representation. An analysis tool was applied to evaluate a variety of scenes from the series. The analysis found that narrative space was of crucial importance for the background of the story and that Madrid played a prominent role in the narrative. Antidisturbios portrays a city that represents the symbolic centre of the Spanish state, understood as a space of hegemonic power that brings together the political and economic elites. At the same time, it presents a contemporary, recognisable, and inclusive geography, which contrasts with the image of the capital in the public and political debate about identity. The city that the series constructs refers to and questions a specific historical period where several of the social problems in current Spanish society are looming.